Student Complaint Management System - Al-waeli, Waleed Sadeq Noman; Hassan, Norlida Binti (Applied Information Technology And Computer Science, 2022)
In the academic context, academic advancement can be of different concerns to strengthen the social and productive education system., for an effective educational system to take place, t certain issues in the academic environment must be properly addressed. Therefore, with the advancement of technology, internet users are increasing exponentially, it would benefit from technology in many things, including the complaints management system in universities. This project identifies a set of options that can be used to manage and collect student complaints. It is possible to design and implement an online complaints management system to benefits the student as well as the university so that the student can share the problems that student faces at the university and the university will be able to solve the student’s problems and provide an appropriate educational environment for all students. This final year project will focus on the development of a complaints management system on the Internet will be for universities that do not have this system, especially universities in Yemen due to the lack of this system. This system works on Monitor student complaints, improve the database, and enhance the effectiveness, safety, and security of the system. The complaints handling system is easily accessible and presented to complainants (the students). The editing software uses brackets, also PHP as the programming language, as well as MySQL as the database. However, the importance of this project will increase more benefits for the students and the University. This system is expected to be easy as students can long to comply at anytime and anywhere. This will make it easier for students to submit complaints from anywhere and at any time.